The Manipulation of Pace within Endurance Sport - Skorski, Sabrina; Abbiss, Chris R. (Frontiers in Physiology, 2017)
In any athletic event, the ability to appropriately distribute energy is essential to prevent premature fatigue prior to the completion of the event. In sport science literature this is termed ‘pacing’. Within the past decade, research aiming to better understand the underlying mechanisms influencing the selection of an athlete’s pacing during exercise has dramatically increased. It is suggested that pacing is a combination of anticipation, knowledge of the end-point, prior experience and sensory feedback. In order to better understand the role each of these factors have in the regulation of pace, studies have often manipulated various conditions known to influence performance such as the feedback provided to participants, the starting strategy or environmental conditions. As with all research there are several factors that should be considered in the interpretation of results from these studies. Thus, this review aims at discussing the pacing literature examining the manipulation of: i) energy expenditure and pacing strategies, ii) kinematics or biomechanics, iii) exercise environment, and iv) fatigue development.